Politics beyond the state: An inquiry into the politics of Filipino everyday-and-ordinary lives - Contreras, Antonio P. (Animo Repository, 2010)
This paper presents the methodological challenges and the specific constraints and opportunities for the conduct of an inquiry into the politics of Filipino everyday-and-ordinary lives. This will be done by giving particular attention to the context of the current dominant discourse and practice in "studying" Philippine society by using Political Science as the disciplinal anchor. Consequently, the current methodological assumptions in Political Science will be interrogated for their enabling and/or disenabling presence relative to how the political is teased out from ordinary and everyday experiences of citizens.